Perkembangan Pendidikan Islam masa Nabi Muhammad SAW Periode Makkah - Rahimi Rahimi (Al-Liqo: Jurnal Pendidikan Islam, 2021)
This study aims to find out how the history and development of education at the time of the Prophet Muhammad SAW. Makkah period, To find out the education system at the time of the Prophet Muhammad. Makkah period, to find out how the methods of education at the time of the Prophet Muhammad SAW. Mecca period and to find out the educational values ​​contained in the da'wah of the Prophet Muhammad SAW during the Mecca period. The research method that is relevant to this context is to use a qualitative research method with a contextual reflective approach, namely the theory found in historical books and verses of the Koran and the Hadiths of the Prophet Muhammad SAW. analyzed or interpreted according to the problem under study. While the results of this study are that, Islamic education has existed since the Prophet Muhammad. alive and it is he who laid the foundation with many examples to take. It can be seen from the production of Islamic generations, as well as found a noble civilization as recorded in world history about the glory of Islamic civilization changing the world from darkness to true enlightenment.